Determining Conceptual Model of Employee Satisfaction and Performance of PT Agung Automall in Soekarno Hatta Pekanbaru - Putra, Rizaldi; Farnila, Vera; Suyono; Tjahjana, Dominicus Josephus Swanto; Renaldo, Nicholas (First Ciera Publisher, 2023)
Human resources are an important asset for the sustainability of an organization or company. Employees with job satisfaction and quality performance will have a positive impact on the company. Therefore PT. Agung Automall at Soekarno Hatta Pekanbaru is very focused on increasing job satisfaction and performance. All of this will certainly have an impact on the sales results made by the company every year. To increase job satisfaction and performance at PT. Agung Automall in Soekarno Hatta Pekanbaru, researchers think it is necessary to do a research analysis on how much positive impact commitment, organizational culture, motivation, leadership style has on job satisfaction and performance at PT. Agung Automall at Soekarno Hatta Pekanbaru. The purpose of the analysis is to determine the appropriate model for determining job satisfaction and performance. In conducting the analysis, the researcher will collect data first, the data collection technique used is to conduct a survey in the form of a questionnaire, where the questionnaire contains questions from each analyzed variable. Data analysis was carried out using Variation Analysis which was processed using SPSS 19.0 and AMOS 21 software. The targeted output of the analysis was that the company would be able to easily find out the weaknesses and strengths of the current company in terms of job satisfaction and performance. related to the company's achievements every year.